The Role of Bonded Areas on Logistics in Low-cost Countries - Qing Lu; Zhengpeng Li; Mark Goh; Robert De Souza (International Journal of Supply Chain Management, 2013)
Globalization opens new possibilities as well as challenges for firms in positioning their productions and sourcing. Many low-cost countries have established various types of bonded areas to attract export-oriented businesses with cost advantages and pro-business policies. As many international firms have moved their operations or key supplies to these areas, bonded areas have been playing critical roles in their supply chain management. Taking China as an example, our study explores the role of bonded areas and highlights the potential drawbacks of bonded areas for international firms. Thirteen respondents with experiences in bonded areas have participated in the study. Policy implications for both international firms and policymakers of low-cost countries are discussed as well.